1984
DOI: 10.1042/bj2170303
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry of reactions of α2-macroglobulin with trypsin and chymotrypsin

Abstract: The stoichiometry of the individual steps, i.e. polypeptide chain cleavage, hydrolysis of the putative thioester bond and conformational change, of the reaction between alpha 2-macroglobulin and trypsin or chymotrypsin was analysed. The chain cleavage was monitored by sodium dodecyl sulphate/polyacrylamide-gel electrophoresis, the thioester hydrolysis by both a spectroscopic and a fluorimetric technique and the conformational change by tryptophan fluorescence. A stoichiometry of close to 2:1 was obtained for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 38 publications
3
40
0
Order By: Relevance
“…The bait region is located approximately in the middle of the polypeptide and, in the case of human ␣ 2 M, contains a sufficient range of different amino acids to make it a suitable "bait" for a wide spectrum of proteinase specificities (41). The efficiency of inhibition is extremely high, such that there is often a stoichiometric relationship between pairs of bait regions cleaved and molecules of proteinase inhibited (42).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bait region is located approximately in the middle of the polypeptide and, in the case of human ␣ 2 M, contains a sufficient range of different amino acids to make it a suitable "bait" for a wide spectrum of proteinase specificities (41). The efficiency of inhibition is extremely high, such that there is often a stoichiometric relationship between pairs of bait regions cleaved and molecules of proteinase inhibited (42).…”
Section: Resultsmentioning
confidence: 99%
“…3B)). Analogously, human ␣ 2 M requires two subunits for inhibition of 1 eq proteinase to give a maximum inhibitory stoichiometry of 2 mol of proteinase per ␣ 2 M tetramer (42).…”
Section: ϫ1 Smentioning
confidence: 99%
“…Trypsin Inhibition Assay-Stoichiometry of trypsin trapping was determined by measuring the soybean trypsin inhibitor-resistant trypsin activity (20,21) at different trypsin:␣ 2 M ratios. ␣ 2 M (120 nM) was incubated with different molar ratios of trypsin for 5 min at 25°C.…”
Section: Site-directed Mutagenesis and Expression Of Recombinant ␣ 2 mentioning
confidence: 99%
“…A stoichiometry of close to 2: 1 was reported for the reaction between trypsin or chymotrypsin and rY.2M by Bjork et a1. 29 ) Steiner et al reported that the equimolar rY. 2 M-thrombin complex contains a second site that is not readily cleaved by thrombin but is accessible to trypsin.…”
Section: Peg 2 -Modijication Of Sepl/mentioning
confidence: 99%